A description of the EU-Greece negotiations through Game Theory. - Spanos, Theofanis (2012)
From the time of the first loaning agreement between Greece and the EU in 2010 until now the country has faced a tremendous economic and social catastrophe. A lot of people in Greece among them major economists like Mr Varoufakis argue that the measures that the EU imposed on Greece in exchange for funding her were so harsh for the country ,that resulted to the country being in depression, and if softer measures were taken, the country would be much better now. So the question is why Greek Government accepted so harsh measures? Could Greece do something better. So what we try to do here is to describe, examine and analyse those negotiations through the use of non-cooperative game theory and by doing so to see whether or not the outcome of those negotiations make sense concerning our analysis with game theory. If not why is that and what else the EU and Greece could do to improve their position and achieve their goals. Specifically this essay is concerned with three different negotiations. The first are the negotiations concerning the first loaning agreement in 2010, the second are the negotiations between Greece and the EU on January and February of 2012 concerning the second loaning agreement and third are the negotiations that take place at the moment between Greece and the EU and they are concerned with the providing of an instalment of 30 billion euros to Greece in exchange for measures that will decrease Greece’s expenses by 12.5 billion euros. Concerning the first loaning agreement the game that better describes her is the battle of sexes . The problem is that what happened in reality is not the same with what Game theory tell us should happen. The explanations we give are related with the inefficiency of Greek politicians that either considers anything that Europe says as credible or they never thought of disagreeing with the EU for reasons that are not related with non-cooperative game theory. Concerning the second loaning agreement the game that describes it better is the chicken. Again the final outcome of the negotiations is not one that a game theorist could expect. The explanation we give is that again Greek consider European /threats and commitments as credible either because they thought that the EU had an interest to look tough on the European countries. Even if that was the case clearly Greece could find ways to countermove that and furthermore could issue a threat for referendum that in our opinion would convince the EU to provide better terms to Greece. Finally concerning the current negotiations Greece is in a very good negotiating position and she could exploit the new program that ECB announced concerning the bonds of countries with problems even if she is not included in it. The example of Italy shows that if you negotiate well and 3 you issue credible threats you can achieve a lot. Greece by issuing threat that she will sue the EU in the European court of justice for being treated unequally with other states could push EU t